The Religious, Social, and Cultural Constraints on Adult Education Research and Practices in Saudi Arabia - Mohammed Awad Alasmrai 8881102 (Adult Education Research Conference, 2016)
Adult educational research and practices in Saudi has faced a number of challenges. These challenges emanate from the environment that surrounds the education sector. Thus, this essay will discuss the constraints in adult education research and practice with special focus on gender-oriented. The purpose of this study will be to explore the impact of the Saudi culture on feminist research in adult education and as well as adult education practices. This paper will answer the following questions: 1) What are the constraints for adult education research and educational planning based on feminist perspectives in Saudi context? 2) How can these constraints be existed while conducting adult education research or educational planning based on feminist perspectives in Saudi context? And 3) What are the possible paths or procedures to overcome these constraints while conducting adult education research or educational planning based on feminist perspectives in Saudi context? In regard to methodology and method, data will be collected using conceptual study. A detailed analysis and review of literature available will be carried out. In addition, several case studies will be provided as evidences. The pre-findings: after reviewing the literature of adult education research concentrated in gender and conducted in Saudi Arabia and concentrated in gender, the social norms and religious norms are two influential factors. In addition, import considerations about gender in doing adult education research in Saudi Arabia are male dominated society, social structures and gender segregation and religious culture. In conclusions, adult education research has influenced by several factors especially when these research is women-oriented in Saudi Arabia. Social structures have an impact on the methodologies and means used by adult researchers to conduct any adult education research. Recently, Saudi educational institutions have rolled out a plan to oversee the inclusion of women in development projects such as educational research.
Keywords: Keywords: Social Constraints- Religious Constraints- Research on Women- Gender segregation - Saudi Arabia